Nāmānukrom phưt kh̨̄ong Yao nai kānkasēt b̄æp tatfan khōn phao : ch̄ư Yao, ch̄ư Thai, ch̄ư witthayāsāt, kānchai prayōt - Čhanthabūn Sutthi (ʻĒkkasān wichākān (Sathāban Wičhai Chāokhao Čhangwat Chīang Mai (Thailand)), 1996)
Plant names of deforest agriculture crops in Yao language and Thai.